EFFECTIVENESS OF QUITLINE SMOKING CESSATION FOR SMOKERS QUIT SMOKING: A LITERATURE REVIEW - Risnadhia, Risnadhia (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
The habit of smoking is a health problem that occurs in various countries. According to The Tobacco Control Atlas ASEAN Region 4th Edition, Indonesia is the country with the largest number of smokersAssociation of Southeast Asian Nations (ASEAN), with a percentage of 36.3% smokers aged between 25-64 years. In WHOReport on the Global Tobacco Epidemic In 2008, there were several policies used to reduce smoking consumption in the world. Quitline Quit Smoking is a telephone counseling service to help people stop smoking. Quitlines are usually available in regional or national services. The literature review aims to determine the effectiveness of the smoking cessation Quitline and what factors influence smoking cessation Quitline. In this literature review, the data used was obtained from electronic databases. The databases used are Scopus, PUBMED, Science Direct, and Google Scholar, using the terms Smokers, Smoking Cessation, Quitline, and Telphone Counseling. The inclusion criteria in this study were research conducted from 2012 to 2023, which discussed the smoking cessation Quitline in English and full text. Results: Based on journals that have been reviewed, all smokers said that they were motivated to quit smoking after using Quitline.